2020
DOI: 10.1186/s40834-020-00131-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of female sterilization method uptake among women of reproductive age group in Uganda

Abstract: Background Despite its great effectiveness, safety and convenience for women who do not wish to have more children; female sterilization method uptake in Uganda is very low. This study aimed at establishing factors associated with female sterilization uptake in Uganda. Methods Secondary data were sourced from the 2016 Uganda Demographic and Health Survey (UDHS). We analyzed all (18,506) women aged 15–49 years who were interviewed in the 2016 UDHS. This sample was categorized into women who were sterilized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
4
6
1
Order By: Relevance
“…Male and female sterilizations are only offered in 5% and 7% of health facilities, respectively [ 20 ] and are not widely accepted, especially in the rural setting. The finding is similar to a study in Uganda that showed that low uptake of these methods were associated with poverty, limited awareness of the method, lack of skilled personnel to administer the method, and limited resources to purchase and maintain laparoscopic equipment [ 57 ]. Poor knowledge and information about the methods, along with religious and socio-cultural barriers, are some of the perceived barriers to the uptake of this method [ 58 ].…”
Section: Discussionsupporting
confidence: 84%
“…Male and female sterilizations are only offered in 5% and 7% of health facilities, respectively [ 20 ] and are not widely accepted, especially in the rural setting. The finding is similar to a study in Uganda that showed that low uptake of these methods were associated with poverty, limited awareness of the method, lack of skilled personnel to administer the method, and limited resources to purchase and maintain laparoscopic equipment [ 57 ]. Poor knowledge and information about the methods, along with religious and socio-cultural barriers, are some of the perceived barriers to the uptake of this method [ 58 ].…”
Section: Discussionsupporting
confidence: 84%
“…Our study showed that the adoption of female sterilization was high in the older cohort than younger ones, and a similar pattern was observed in all the states, and covariates, except for Tamil Nadu, where it was observed a similar trend of female sterilization in all the birth cohort. With similar studies, newer cohorts generally rely on the spacing methods of family planning as they are more educated and still in the reproductive age groups [ 47 ]. Also, education have a major role in the contraception adoption in India.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is reported similarly in studies done in Uganda, in central and eastern provinces of Kenya and Kwara State, Nigeria where the studies reported that socio-cultural influences as the main determinants of BTL uptake. 22 , 28–30 …”
Section: Discussionmentioning
confidence: 99%